Математичнi моделi алгоритмiв i реалiзацiя Ateb-функцiй - Грицик, В.В.; Назаркевич, М.А. (Видавничий дім "Академперіодика" НАН України, 2007)
An oscillatory nonlinear system whose required parameters vary in time by a nonsinusoidal aperiodic law is considered.